2014
DOI: 10.1111/nph.13161
|View full text |Cite
|
Sign up to set email alerts
|

Repression of flowering under a noninductive photoperiod by the HDA9AGL19FT module in Arabidopsis

Abstract: SummaryPosttranslational acetylation of histones is reversibly regulated by histone deacetylases (HDACs). Despite the evident significance of HDACs in Arabidopsis development, the biological roles and underlying molecular mechanisms of many HDACs are yet to be elucidated.By a reverse-genetic approach, we isolated an hda9 mutant and performed phenotypic analyses on it. In order to address the role of HDA9 in flowering, genetic, molecular, and biochemical approaches were employed.hda9 flowered early under nonind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(103 citation statements)
references
References 71 publications
5
96
1
1
Order By: Relevance
“…S3) (35, 36). The early flowering phenotype was much milder under continuous light compared with short-day conditions (35,36), such that pwr-2 and hda9-1 mutants bolted about 1.5 d earlier than wild type, with a similar number of rosette leaves to that in wild type at bolting (Fig. S3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S3) (35, 36). The early flowering phenotype was much milder under continuous light compared with short-day conditions (35,36), such that pwr-2 and hda9-1 mutants bolted about 1.5 d earlier than wild type, with a similar number of rosette leaves to that in wild type at bolting (Fig. S3).…”
Section: Resultsmentioning
confidence: 99%
“…2B). Several studies have shown that early flowering in hda9 is because of increased AGL19 levels, which results from increased levels of histone acetylation and Pol II occupancy at the locus (35,36). To investigate whether PWR acts in the AGL19-mediated floweringtime pathway through HDA9 function, we first examined AGL19 transcript levels in pwr-2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4). In contrast, hda9 mutants display an early flowering phenotype under short-day conditions [33]. HDA9 directly represses the expression of AGOMOUS-LIKE 19 (AGL19), an upstream activator of FT through histone deacetylation.…”
Section: Regulation Of Flowering Timementioning
confidence: 97%
“…AGL19, another MADS-box protein closely related to SOC1, might also play a role in the vernalization pathway, as the agl19 and flc mutations show additive impairment of the vernalization response (Schönrock et al, 2006). AGL19 appears to be a floral activator up-regulated upon cold exposure through FLC-independent processes (Schönrock et al, 2006;Kang et al, 2015). Although further work is needed to assess the role of these additional components in the vernalization response, a recent study suggests that they might participate in environmental adaptation as their differential regulation is correlated with the flowering time of different accessions originating from an altitudinal gradient (Suter et al, 2014).…”
Section: The Memory Of Winter In Arabidopsismentioning
confidence: 99%